Kearifan Lokal Permainan Jamuran sebagai Penguatan Karakter Siswa melalui Layanan Bimbingan Konseling - Syofiyanti, Dessy; Marjuk, Yolan (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2023)
The development of technology affects the games played by students through gadgets. Many interesting games can have a negative impact, such as the lack of socialization of students with their friends, emotional disturbances, behavior, and others. This study aims to instill character education through traditional “mushroom games” with a Counseling Guidance approach at Pertiwi Rengat Kindergarten. This research is qualitative research with Miles and Huberman model analysis techniques. The results showed that students’ behavior changed, such as throwing garbage in its place, greeting each other, and shaking hands with teachers and other people (guests at school) when meeting face-to-face. In addition, observations showed that the students looked happy when doing activities together. Thus, traditional mushroom games with a group guidance approach can be used to instill students’ character to be even better.